Lower serum levels of IL-1β and IL-6 cytokines in adolescents with anorexia nervosa and their association with gut microbiota in a longitudinal study - Specht, Hannah E.; Mannig, Nina; Belheouane, Meriem; Andreani, Nadia Andrea; Tenbrock, Klaus; Biemann, Ronald; Borucki, Katrin; Dahmen, Brigitte; Dempfle, Astrid; Baines, John F.; Herpertz-Dahlmann, Beate; Seitz, Jochen (Frontiers in Psychiatry, 2022)
Introduction: Anorexia nervosa (AN) is an often chronic and debilitating psychiatric disease whose aetiology is not completely understood. Recently, a potential role of inflammation has emerged in other psychiatric diseases, such as depression, PTSD and schizophrenia. The first results in adults with AN seemed to confirm a low-grade proinflammatory state until recent studies presented more differential findings. Studying adolescents with a shorter illness duration and fewer confounding factors might help elucidate the role of inflammation in the underlying pathophysiology of AN; however, the few available studies in adolescents remain ambiguous, and no longitudinal data are available in this age range. Methods: We examined the proinflammatory cytokines Tumor Necrosis Factor-alpha (TNF-⍺), Interleukin (IL)-1β, IL-6, IL-15 and the cytokine-receptor IL-6 Receptor alpha (IL-6 R⍺) in the serum of twenty-two hospitalised female adolescent patients with AN longitudinally at admission and discharge and compared their results to nineteen healthy controls (HC). We also collected clinical data and stool samples that were analysed with 16S rRNA amplicon sequencing to explore potential influencing factors of cytokine changes. Results: TNF-⍺ serum levels were significantly elevated in patients with AN at admission, while IL-1β and IL-6 levels were lower at admission and discharge than in HC. After treatment, we also found significantly elevated levels of IL-6 R⍺ compared to HC, while IL-15 did not show significant changes. Exploratory analyses revealed positive associations of cytokine and genus-level changes between admission and discharge for IL-1β (Bacteroides) and IL-15 (Romboutsia), and negative associations for IL-15 (Anaerostipes) and TNF-⍺ (uncultured Lachnospiraceae). Conclusions: We confirmed a previous finding of elevated levels of TNF-⍺ also in adolescents with AN; however, the reduced IL-1β and IL-6 levels differed from the mostly increased levels found in adults. A mixed pro- and anti-inflammatory state appears to be present in adolescents, potentially due to their shorter illness duration. The gut microbiota, with its regulatory function on cytokine production, might play a role in mediating these inflammatory processes in AN and could offer targets for new therapeutic approaches.